High Yield of Adult Oligodendrocyte Lineage Cells Obtained from Meningeal Biopsy - Dolci, Sissi; Pino, Annachiara; Berton, Valeria; Gonzalez, Pau; Braga, Alice; Fumagalli, Marta; Bonfanti, Elisabetta; Malpeli, Giorgio; Pari, Francesca; Zorzin, Stefania; Amoroso, Clelia; Moscon, Denny; et al. (Frontiers in Pharmacology, 2017)
Oligodendrocyte loss can lead to cognitive and motor deficits. Current remyelinating therapeutic strategies imply either modulation of endogenous oligodendrocyte precursors or transplantation of in vitro expanded oligodendrocytes. Cell therapy, however, still lacks identification of an adequate source of oligodendrocyte present in adulthood and able to efficiently produce transplantable cells. Recently, a neural stem cell-like population has been identified in meninges. We developed a protocol to obtain high yield of oligodendrocyte lineage cells from one single biopsy of adult rat meningeal tissue. From 1 square centimeter of adult rat spinal cord meninges, we efficiently expanded a homogenous culture of 10 millions of meningeal-derived oligodendrocyte lineage cells in a short period of time (approximately 4 weeks). Meningeal-derived oligodendrocyte lineage cells show typical mature oligodendrocyte morphology and express specific oligodendrocyte markers, such as galactosylceramidase and myelin basic protein. Moreover, when transplanted in a chemically-demyelinated spinal cord model, meningeal-derived oligodendrocyte lineage cells display in vivo-remyelinating potential. This oligodendrocyte lineage cell population derives from an accessible and adult source, being therefore a promising candidate for autologous cell therapy of demyelinating diseases. In addition, the described method to differentiate meningeal-derived neural stem cells into oligodendrocyte lineage cells may represent a valid in vitro model to dissect oligodendrocyte differentiation and to screen for drugs capable to promote oligodendrocyte regeneration.